Advances in wireless sensor networks 6th China Conference, CWSN 2012, Huangshan, China, October 25-27, 2012, revised selected papers - Xiao, Fu; Wang, Ruchuan (Communications in Computer and Information Science,, 2013)
This book constitutes the refereed proceedings of the 6th China Conference on Advances in Wireless Sensor Networks, held in Huangshan, China, in October 2012. The 70 revised full papers were carefully reviewed and selected from 458 submissions. The papers cover a wide range of topics including in the wireless sensor network fields nodes systems, infrastructures, communication protocols, and data management.